2004
DOI: 10.1179/016164104773026633
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol intoxication in a model of traumatic brain injury: The protective role of moderate doses demonstrated by immunoreactivity of synaptophysin in hippocampal neurons

Abstract: Although ethanol intoxication is reported to be a complicating factor in traumatic brain injury, some recent studies are indicating its possible protective role especially at lower doses. Ethanol inhibition of NMDA-mediated excitotoxicity which predominates at lower doses is believed to be responsible for this protection. The aim of this study was to demonstrate this neuroprotective role of alcohol using immunoreactivity for synaptophysin as an indirect marker for severity of injury. Acute ethanol intoxication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…At high doses (Ͼ240 mg/ dL), alcohol was shown in animal studies to be deleterious to neurologic outcomes. [10][11][12][13] In our study, a BAC of 230 mg/dL or greater was shown to be associated with higher mortality than a BAC of 0. Also, there was a trend in both our study group and in our tracer group to suggest that patients with a high BAC were more likely to die earlier after trauma compared with patients with no BAC.…”
Section: Commentmentioning
confidence: 58%
“…At high doses (Ͼ240 mg/ dL), alcohol was shown in animal studies to be deleterious to neurologic outcomes. [10][11][12][13] In our study, a BAC of 230 mg/dL or greater was shown to be associated with higher mortality than a BAC of 0. Also, there was a trend in both our study group and in our tracer group to suggest that patients with a high BAC were more likely to die earlier after trauma compared with patients with no BAC.…”
Section: Commentmentioning
confidence: 58%
“…Low dose ethanol inhibition of N-methyl-D-aspartate (NMDA) receptors could be neuroprotective as potassium and calcium influx through NMDA receptor channels following TBI leads to neuronal excitotoxicity [9][10][11][12][13]. The systemic catecholamine surge following TBI which is associated with worse outcomes has been shown to be moderated by ethanol [14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…have suggested that alcohol might have a neuroprotective effect on the brain following traumatic brain injury (TBI) through such mechanisms as inhibiting N-methyl-Daspartate (NMDA) receptor-mediated excitotoxicity (Cebere and Liljequist, 2003;Chandler et al, 1993;Is et al, 2005;Türeci et al, 2004), decreasing the degree of uncoupling between glucose metabolism and cerebral blood fl ow (Kelly et al, 2000), inhibiting the production of pro-infl ammatory cytokines (Gottesfeld et al, 2002), attenuating TBI-induced hyperthermia (Taylor et al, 2002), and blunting the sympathoadrenal response in TBI (Opreanu et al, 2010). Premised on the evidence from animal research, one recent study confi rmed that patients who were intoxicated at the time of injury had better acute neuropsychological outcomes when recovering from TBI than did nonintoxicated patients (Lange et al, 2008).…”
Section: S Everal Animal and Laboratory Studiesmentioning
confidence: 99%